Comparative genomic profiling of transport inhibitor Response1/Auxin signaling F-box (TIR1/AFB) genes in eight Pyrus genomes revealed the intraspecies diversity and stress responsiveness patterns - Yang, Sheng; Yu, Xiaomei; Gao, Xinke; Fatima, Kinza; Tahir Ul Qamar, Muhammad (Frontiers in Genetics, 2024)
Pyrus (pear) is among the most nutritious fruits and contains fibers that have great health benefits to humans. Pears are highly subjected to biotic and abiotic stresses which affect their yield. TIR1/AFB proteins act as auxin co-receptors during the signaling of nuclear auxins and play a primary role in development-related regulatory processes and responses to biotic and abiotic stresses. However, this gene family and its members have not been explored in Pyrus genomes, which will help obtain useful insights into stress tolerance and ultimately help maintain a high yield of pears. This study reports a pangenome-wide investigation of TIR1/AFBs genes from eight Pyrus genomes: Cuiguan (Pyrus pyrifolia), Shanxi Duli (P. betulifolia), Zhongai 1 [(P. ussuriensis × communis) × spp.], Nijisseiki (P. pyrifolia), Yunhong No.1 (P. pyrifolia), d’Anjou (P. communis), Bartlett v2.0 (P. communis), and Dangshansuli v.1.1 (P. bretschneideri). These genes were randomly distributed on 17 chromosomes in each genome. Based on phylogenetics, the identified TIR1/AFB genes were divided into six groups. Their gene structure and motif pattern showed the intraspecific structural conservation as well as evolutionary patterns of Pyrus TIR1/AFBs. The expansion of this gene family in Pyrus is mainly caused by segmental duplication, however, fewer genes showed tandem duplication. Moreover, positive and negative selection pressure equally directed the gene's duplication process. The GO and PPI analysis showed that Pyrus TIR1/AFB genes are associated with abiotic stress- and development-related signaling pathways. The promoter regions of Pyrus TIR1/AFBs genes were enriched in hormones-related, light, development, and stress-related cis-elements. Furthermore, publicly available RNA-seq data analysis showed that DaTIR1/AFBs have varied levels of expression in various tissues and developmental stages, fruit hardening disease conditions, and drought stress conditions. This indicated that DaTIR1/AFBs genes might play critical roles in response to biotic and abiotic stresses. .The DaTIR1/AFBs have similar protein structures which show that they are involved in the same function also. Hence, this study will broaden our knowledge of the TIR1/AFB gene family in Pyrus, elucidating their contribution to conferring resistance against various environmental stresses, and also will serve as valuable insights for future researchers.